Proposal for improving the warehouse management of a ruber packing producer company applying the 5 "S" - Hinostroza Gayoso, Iriana Jhazmin (2023)
The objective of the research is to allocate the time saved, thanks to the improvement, to the production activity by increasing the efficiency that allows the greatest number of tasks to be carried out without altering the quality of the product. The main causes found thanks to the study carried out were the non-existence of a labeling system, lack of space, incorrect information system and storage equipment in poor condition. This in order to carry out an analysis and a subsequent proposal for each stage: Seiri, Seiton, Seiso, Seiketsu and Shitsuke. The new layout of each warehouse, Raw Material and Finished Product was proposed. The results indicate that the time allocated to carry out warehouse activities is 396.22 hours per month and, after the analysis, the new time that will be obtained is 209.35 hours, managing to reduce the total time by 186.88 hours; that is, 47.16%. Thus, the number of additional rubber gaskets that will be produced will be approximately 86,328.